Meningkatkan Kemampuan Sosial Emosional Anak Usia Dini Melalui Penggunaan Reward Dan Punishment Di TK Persis 451 Al-I’tishom - Fauziah, Irna Rahmawati; Chalid, Choriyah; Azzahri, Childa Kumala (CV. ITTC INDONESIA, 2024)
Improving Early Childhood Social Emotional Abilities Through the Use of Rewards and Punishments in Kindergarten Persis 451 Al-I'tishom (2024). Thesis. Bekasi: Panca Sakti University Bekasi. 2024. This research aims to improve the social and emotional abilities of early childhood through the use of rewards and punishment in Kindergarten Persis 451 Al-I'tishom. To obtain data by implementing it in group A, the research method used was the classroom action research method. The subjects of this research were 13 group A children consisting of 8 boys and 5 girls. The data used were observations, field notes, observation sheets and documentation. Data analysis techniques were carried out descriptively, qualitatively and quantitatively. The indicator of success in this research is said to be successful if the emotional abilities of young children in the Very Well Developing category have reached a percentage of 85%. The results of the study showed that children's abilities in the pre-cycle reached 50%, the first cycle reached 60.6%, and the second cycle reached 85%. Thus there was an increase from pre-cycle to cycle I and cycle II. This research can be concluded that the reward and punishment method can be applied to improve social emotional skills in children aged 4-5 years at Kindergarten Persis 451 Al-I'tishom. With the reward and punishment method, children can be interactive and full of hope because with this method children can answer the teacher's questions because of the rewards and punishments that these children will receive. The results of this research provide important meaning for the development of educational policies, especially related to improving the quality of children's learning outcomes.